Traumatic chain: Korean–American immigrants’ transgenerational language and racial trauma in Native Speaker - Ahmad, Muhammad Sohail; Nawaz, Shazmeen; Bukhari, Zainab; Nadeem, Mubashar; Hussain, Rana Yassir (Frontiers in Psychology, 2022)
The premise of this study is to look at the intergenerational transferal of language and racial trauma of Asian immigrants in general and Korean–American immigrants in particular to a western country, the United States of America. This study investigates trauma from a psychological standpoint, based on Chang-Rae Lee’s novel Native Speaker. In describing a marker of citizenship, the novel’s title also points to who is the native language speaker and who is a native of a country, and why one who is not may be excluded. The Korean immigrants’ vulnerability to the English language and racial differences highlights their status as minority “others,” and they suffer from transgenerational trauma. As a result of transgenerational traumatic effects, Henry (the protagonist) has various traumatic side effects such as dysphasia, aphasia, and parasomnia and finally leaves no stone unturned to recuperate from trauma. The Trauma of the Unspeakable theory by Michelle Balaev is used in this article to show how trauma affects people’s minds.